Measuring the contribution of international remittances to household expenditures and economic output: A micro-macro analysis for the Philippines - Aiko Kikkawa; Raymond Gaspar; Kijin Kim; Mahinthan J. Mariasingham; Christian Marvin Zamora (Asian Development Bank (ADB), 2024)
The macroeconomic studies that assess the contribution of international remittances to the origin countries of migrants use a different definition of remittances than the microeconomic literature that examines the impact at the household and community levels. This study overcomes this difference in definition by integrating household expenditure data into the input-output analysis. Using the 2018 Family Income and Expenditure Surveys (FIES) of the Philippines, we find that remittance-financed household consumption and investment totaled ₱742.2 billion (14.1 billion) and contributed 3.5% of the country's total output, 3.4% of gross domestic product (GDP), and 3.7% of total employment in 2018. We note that the largest value added is accruing to the manufacturing sector as it accounts for more than a third of remittance recipients' spending basket followed by the trade and agriculture, forestry, and fisheries sectors, which are closely linked to the manufacturing industry. The international remittances income reported by households is less than half (43.8%) of the ₱1.7 trillion (32.2 billion) aggregate international remittances reported by the central bank in the same year based on the balance of payments definition.
Keywords: F24; C67; D12; 330; international remittance; household expenditure; micro-macro analysis; Philippines